Erratum: Measurement of CP observables in B±→DK[star]± decays using two- and four-body D final states - Aaij, Roel; D'Argent, Philippe; Bachmann, Sebastian; Berninghoff, Daniel; Braun, Svende; Comerma-Montells, Albert; De Cian, Michel; Dziewiecki, Michal; Gerick, David; Grabowski, Jascha; Han, Xiaoxue; Hansmann-Menzemer, Stephanie; et al. (Journal of high energy physics, 2018)
The measurements of Aππ and RKK in B±→DK*± decays were incorrectly reported in the paper [1], due to a transposition of the systematic uncertainties. This error was present in the reporting of the individual systematic uncertainties, the correlation matrix, and in the calculation of RCP+.